The topography of cortical microbleeds in frontotemporal lobar degeneration: a post-mortem 7.0-tesla magnetic resonance study - Jacques De Reuck; Florent Auger; Nicolas Durieux; Vincent Deramecourt; Claude-Alain Maurage; Florence Lebert; Didier Leys; Charlotte Cordonnier; Florence Pasquier; Regis Bordet (Folia Neuropathologica, 2016)
Introduction : Cerebrovascular lesions are rare in frontotemporal lobar degeneration (FTLD), in contrast to other neurodegenerative diseases. Cortical microbleeds (CoMBs) are frequent in Alzheimer’s disease, in particular in cases associated with cerebral amyloid angiopathy. The present study investigates the gyral topographic distribution of CoMBs in post-mortem FTLD brains with 7.0-tesla magnetic resonance imaging. Material and methods : The distribution of CoMBs in 11 post-mortem FTLD brains and in 12 control brains was compared on T2*-GRE MRI of six coronal sections of a cerebral hemisphere. The mean values of CoMBs were determined in twenty-two different gyri. The findings were correlated to those separately observed on neuropathological examination. Results : As a whole there was a trend of more CoMBs in the prefrontal section of FTLD as well as of the control brains. CoMBs were significantly increased in the superior frontal gyrus and the insular cortex (p ≤ 0.001) and also in the inferior frontal gyrus and the superior temporal gyrus (p ≤ 0.01). Conclusions : CoMBs in FTLD are only increased in the regions mainly affected by the neurodegenerative lesions. They probably do not reflect additional cerebrovascular disease.